Executive Function in Previously Institutionalized Children. (19th February 2016) - Merz, Emily C.; Harlé, Katia M.; Noble, Kimberly G.; McCall, Robert B.
Abstract: In studies of children adopted from institutions, early institutionalization has been associated consistently with an increased risk of persistent cognitive, academic, and social‐emotional problems. These findings raise questions about the neurocognitive mechanisms that contribute to these negative outcomes. Theory and models based on studies of animals indicate that development of the prefrontal cortex (PFC) and executive function (EF) may be particularly susceptible to environmental influences during early childhood. In this article, we review recent studies of postinstitutionalized children that examined EF components such as inhibitory control, working memory, shifting, and planning. We then describe emerging research on the structure and function of the PFC. Converging evidence suggests both EF difficulties and alterations in development of the PFC following early institutionalization. We conclude by discussing possible explanations for these findings and implications for prevention and intervention, and by offering suggestions for ongoing research.